Reconstitution of SPO11-dependent double-strand break formation - Zhi Zheng; Lyuqin Zheng; Meret Arter; Kaixian Liu; Shintaro Yamada; David Ontoso; Soonjoung Kim; Scott Keeney (Nature, 2025)
Abstract Meiotic recombination starts with SPO11 generation of DNA double-strand breaks (DSBs) 1 . SPO11 is critical for meiosis in most species, but it generates dangerous DSBs with mutagenic 2 and gametocidal 3 potential. Cells must therefore utilize the beneficial functions of SPO11 while minimizing its risks 4 —how they do so remains poorly understood. Here we report reconstitution of DNA cleavage in vitro with purified recombinant mouse SPO11 bound to TOP6BL. SPO11–TOP6BL complexes are monomeric (1:1) in solution and bind tightly to DNA, but dimeric (2:2) assemblies cleave DNA to form covalent 5′ attachments that require SPO11 active-site residues, divalent metal ions and SPO11 dimerization. SPO11 can also reseal DNA that it has nicked. Structure modelling with AlphaFold 3 suggests that DNA is bent prior to cleavage 5 . In vitro cleavage displays a sequence bias that partially explains DSB site preferences in vivo. Cleavage is inefficient on complex DNA substrates, partly because SPO11 is readily trapped in DSB-incompetent (presumably monomeric) binding states that exchange slowly. However, cleavage is improved with substrates that favour dimer assembly or by artificially dimerizing SPO11. Our results inform a model in which intrinsically weak dimerization restrains SPO11 activity in vivo, making it exquisitely dependent on accessory proteins that focus and control DSB formation.